The psychological contract, performance and satisfaction of employees of public and private organizations of Lima - Loli, Alejandro (2017)
Theorists and researchers have agreed that the psychological contract is a process that refers to reciprocal and implicit obligations between the employee and the employer, and goes beyond explicit and / or formal contracts. This situation, which remained stable before the 1990s, is becoming more important in the present times, due to sudden changes in the modality of jobs in the current organizations. For that reason, the objective of the present study is to know the current state of the psychological contract and its relationship with performance and satisfaction in 303 employees of the public and private sector of Lima. The results show that there is a significant and positive correlation between psychological contract, performance and satisfaction. In the meantime, there are differences between the obligations of the organization according to whether public or private, impacting more on private organizations; happening in the same way with job satisfaction. Similar differences were found among study variables according to gender, marital status, occupational status, wages and place of residence; however the results are different when variables such as age, years of service in the position and seniority in the organization are analyzed.